Preoperative evaluation of conservative surgery in gynecology - Poch, Luis Andrés (Cirugía del Uruguay, 1973)
In order to reach it goal conservative gynaecological surgery, requires a complete an¡:I detailed preoperatory test which in future can keep the patient free any patological process. Once genital cancer and infection have been discarded, the .anatornical and functional aspects of the patient's genital apparatus should be studied, as well as her psychic-neuroendocrinal characteristics. Clinical data must be completed with paraclinical tests. Auxiliary tests both have benefits and limitations. Greater accuracy is obtained when the test's results are situated on the same diagnostical line. Nowadays, laparoscopy is the most developed and frequently used gynaecological exam.